The Use of 99mTc-Methoxy-isobutyl-isonitrile (sestaMIBI) Uptake on Scintigraphy (99m-STS) in Amiodarone-Induced Thyrotoxicosis: Case Series and Review of the Literature - Ghada Elshimy; Mahmoud Alsayed; Jerome Targovnik; Gamal Sidarous; Kresimira M. Milas (Case Reports in Endocrinology)
Amiodarone is a class III antiarrhythmic drug, used by cardiologists to treat arrhythmia including atrial fibrillation (A fib) and ventricular fibrillation. However, amiodarone is associated with endocrine dysfunction including both hypo- and hyperthyroidism. In the literature, two types of amiodarone-induced thyrotoxicosis (AIT) were described: AIT-1 and AIT-2. Mixed AIT also called AIT type 3 (AIT-3) has been described in the literature when the cases do not have a typical presentation. In order to differentiate different types of AIT, various clinical, biochemical, and radiological tools have been proposed. The use of 99mTc-methoxy-isobutyl-isonitrile (sestaMIBI) uptake on scintigraphy (99m-STS) has been suggested in the literature in only few studies (no large retrospective or prospective studies have been established in the United States). We present a case series describing 5 patients presenting to the University of Arizona with AIT where we used 99m-STS to assess in diagnosis and treatment of different types of AIT followed by a review of the literature.